2014
DOI: 10.1589/jpts.26.997
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer and Gyroscope Based Gait Analysis Using Spectral Analysis of Patients with Osteoarthritis of the Knee

Abstract: [Purpose] A wide variety of accelerometer tools are used to estimate human movement, but there are no adequate data relating to gait symmetry parameters in the context of knee osteoarthritis. This study’s purpose was to evaluate a 3D-kinematic system using body-mounted sensors (gyroscopes and accelerometers) on the trunk and limbs. This is the first study to use spectral analysis for data post processing. [Subjects] Twelve patients with unilateral knee osteoarthritis (OA) (10 male) and seven age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…14,15 Comparing the performance of an accelerometer-based to a multisensor-based monitor will also provide evidence for informed decisions of clinicians and researchers when choosing a monitor to measure PA in people with similar characteristics. The purpose of this study was to determine the concurrent criterion-related validity of two activity monitors against indirect calorimetry in measuring energy expenditure during sedentary to moderate intensity activities in older adults after TKA, and we hypothesized similar validity of both activity monitors.…”
mentioning
confidence: 99%
“…14,15 Comparing the performance of an accelerometer-based to a multisensor-based monitor will also provide evidence for informed decisions of clinicians and researchers when choosing a monitor to measure PA in people with similar characteristics. The purpose of this study was to determine the concurrent criterion-related validity of two activity monitors against indirect calorimetry in measuring energy expenditure during sedentary to moderate intensity activities in older adults after TKA, and we hypothesized similar validity of both activity monitors.…”
mentioning
confidence: 99%
“…Postural visual dependence: Postural visual dependence was assessed by postural sway acceleration (m/s2), which was measured using a smartphone device (Apple iPhone 4s, Apple Computer Inc., USA) loaded with the SPARKvue Application software (v2.5.0, PASCO Scientific, USA). The iPhone device was firmly attached to the subject by means of an elastic belt around the waist over the middle part of the lower back over the L3 (3rd lumbar) vertebra process so that it was attached close to the center of gravity (COG) of the human body [8]. Several studies have indicated that accelerometric mobile devices, such as an iPhone or iPod, showed the capacity to quantify balance parameters with accuracy and reliability [9] when compared to laboratory equipment such as strain gauges and accelerometers.…”
Section: Methodsmentioning
confidence: 99%
“…The various accelerometer designs are sensitive and have diverse dynamic ranges [ 6 , 17 19 ]. Accelerometer-based gait analysis has potential application in rehabilitation and clinical practice settings, as well as in research [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…FFT calculates the component frequencies of a signal and the amount of movement (amplitude) at each frequency. The summation of a number of sine and cosine waves of different frequencies and amplitudes generated from the motion of different physical structures can be considered as a frequency signal resulting from ground reaction forces [ 25 ]. If the subjects with TKA produce slight motion instability, FFT can detect it as a frequency signal provided by ground reaction forces.…”
Section: Introductionmentioning
confidence: 99%